Intra-uterine Growth Restriction Downregulates the Hepatic Toll Like Receptor-4 Expression and Function - Ozlem Equils; Sapna Singh; Semra Karaburun; Daning Lu; Manikkavasagar Thamotharan; Sherin U. Devaskar (Clinical and Developmental Immunology)
Maternal starvation is a significant cause of intrauterine growth restriction (IUGR) in the world and increases the risk of infection in the neonate. We examined the effect of maternal starvation on Toll like receptor (TLR)4 expression in hepatic, splenic and intestinal tissues obtained from the adult IUGR offspring of prenatal calorie restricted rats. The hepatic TLR4 protein concentration was undetectable in the IUGR rats that had restricted milk intake during the suckling period (SM/SP; n = 4, p < 0.05) as compared to the normal growth controls (CM/CP; n=4), and access to ad lib milk intake during the sucking period partially corrected the hepatic TLR4 expression (SM/CP; n = 4). IUGR had no effect on the splenic (n = 4) or intestinal (n = 4) TLR4 mRNA levels. In the liver, IUGR led to a 20% increase in baseline tumor necrosis factor (TNF)-α mRNA expression ( p < 0.03) and a 70% increase in interleukin-1β (IL-1β) mRNA expression ( p < 0.008) as compared to the control rats (CM/CP; n = 7). LPS-induced hepatic TNF-α release was significantly higher in SM/SP as compared to CM/CP. We propose that IUGR dysregulates TLR4 expression and function in the offspring, which may help explain the increased risk of Gram-negative sepsis and inflammatory diseases in this population.